ON THE ISSUE OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE AT THE ELEMENTARY LEVEL - Tuychibaeva , Sh.Sh. (Innovative Development in Educational Activities, 2023)
This article examines one of the most important aspects of teaching Russian as a foreign language. The purpose of the article is to reveal the role of mastering skills that affect the process of communication and mastering the Russian language in general. During the research, comparative and descriptive methods were used. The author reveals the purpose of the introductory phonetic course, where the foundations of speech hearing and pronunciation are laid. It is indicated that an introductory phonetic course can be built with or without taking into account the native language of students; when teaching pronunciation, a special technique is needed, focused not only on correcting, but also on preventing errors. The groups of exercises used to develop the skills of correct pronunciation are highlighted. The author also reveals the main difficulties faced by foreign listeners. The orthoepic norms of the Russian language associated with the pronunciation of vowels and consonants, staging of stress and intonation are considered. Recommendations are given on the organization of work on practicing pronunciation.